Updating targets for natural killer/T-cell lymphoma immunotherapy - Xue, Weili (Cancer Biol Med, 2021)
Natural killer/T-cell lymphoma (NKTCL) is a highly invasive subtype of non-Hodgkin lymphoma, typically positive for cytoplasmic CD3, CD56, cytotoxic markers, including granzyme B and TIA1, and Epstein-Barr virus (EBV). The current treatment methods for NKTCL are associated with several drawbacks. For example, chemotherapy can lead to drug resistance, while treatment with radiotherapy alone is inadequate and results in frequent relapses. Moreover, hematopoietic stem cell transplantation exhibits limited efficacy and is not well recognized by domestic and foreign experts. In recent years, immunotherapy has shown good clinical results and has become a hot spot in cancer research. Clinical activity of targeted antibodies, such as daratumumab (anti-CD38 antibody) and brentuximab vedotin (anti-CD30 antibody), have been reported in NKTCL. Additionally, dacetuzumab and Campath-1H have demonstrated promising results. Further encouraging data have been obtained using checkpoint inhibitors. The success of these immunotherapy agents is attributed to high expression levels of programmed death-ligand 1 in NKTCL. Furthermore, anti-CCR4 monoclonal antibodies (mAbs) exert cytotoxic actions on both CCR4+ tumor cells and regulatory T cells. Depletion of these cells and the long half-life of anti-CCR4 mAbs result in enhanced induction of antitumor effector T cells. The role of IL10 in NKTCL has also been investigated. It has been proposed that exploitation of this cytokine might provide potential novel therapeutic strategies. Cellular immunotherapy with engineered cytotoxic T lymphocytes targeted against LMP1 and LMP2 has shown promising results and sustained remission. Cellular immunotherapy may be used either as maintenance therapy following initial induction chemotherapy or in cases of relapsed/refractory disease. The present review outlines the known immunotherapy targets for the treatment of NKTCL.